Interface preassembly oriented growth strategy towards flexible crystalline covalent organic framework films for OLEDs - Li, Xiang-Chun; Sun, Hao; Wang, Zuqiang; Yang, Weijie; Wang, Qiaoyu; Wu, Chuanrui; Chen, Jiajun; Jiang, Qinchen; He, Ling-Jun; Xue, Qian; Huang, Wei; Lai, Wen-Yong (Nature communications, 2025)
The synthesis of flexible crystalline films for optoelectronic applications remains a significant chemical challenge due to the inherent contradiction between flexibility and crystallinity. The delicate balance between flexibility and crystallinity has long constituted a barrier to the development of high-performance optoelectronic materials. Herein, an interface preassembly oriented growth (IPOG) strategy has been explored to fabricate flexible crystalline covalent organic framework (COF) films with controllable thickness. By synergistically modulating hydrophilic and hydrophobic interactions along with interfacial confinement, a set of uniform and flexible crystalline COF films were successfully synthesized. This achievement unlocks the potential of COFs for device applications in organic light-emitting diodes, leading to unprecedented high-efficiency electroluminescence from COFs. This groundbreaking advancement not only lays the foundation for the progress of COF-based OLEDs but also signifies the advent of an era in the synthesis of flexible crystalline materials, wherein exceptional mechanical properties are seamlessly integrated with superior electronic performance, thus heralding a transformative impact on the landscape of flexible electronics. Flexible optoelectronic materials are limited by the optimization of both high crystallinity and flexibility. Here, the authors demonstrate an interface preassembly oriented growth strategy for constructing flexible crystalline covalent organic framework films.